1995
DOI: 10.3171/jns.1995.82.5.0772
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coregistration of MR to CT images on MR stereotactic accuracy

Abstract: Coregistration of different modality imaging serves to increase the ease and accuracy of stereotactic procedures. In many cases, magnetic resonance (MR) stereotaxis is supplanting computerized tomography (CT). The advantages of increased anatomical detail and multiplanar imaging afforded by MR, however, are offset by its potential inaccuracy as well as the more cumbersome and less available nature of its hardware. A system has been developed by one of the authors by which MR imaging can be performed separately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…For the STN-DBS patients, the mean preoperative L -dopa response was 52.55% and the mean L -dopa response status was 14.25 [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19]. The mean UPDRS III improvement at 6 months was 75% (mean ‘off med' score before surgery = 30.8 [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45], mean score ‘on stim/on med' = 7.8 [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17], mean ‘on stim/off med' score after 6 months = 14.15 [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26]). There was neither mortality nor morbidity (permanent nor transient) related to the DBS surgeries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the STN-DBS patients, the mean preoperative L -dopa response was 52.55% and the mean L -dopa response status was 14.25 [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19]. The mean UPDRS III improvement at 6 months was 75% (mean ‘off med' score before surgery = 30.8 [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45], mean score ‘on stim/on med' = 7.8 [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17], mean ‘on stim/off med' score after 6 months = 14.15 [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26]). There was neither mortality nor morbidity (permanent nor transient) related to the DBS surgeries.…”
Section: Resultsmentioning
confidence: 99%
“…In all these cases, there was no remaining error measurable on the planning software. The remaining stereotactic errors are thus mostly linked to errors in image matching between the MRI and the CT scan [16], [35,36,37,38] and, to some extent, a brain shift error when placing the needle or electrode in the brain [39]. Matching between CT and MRI data sets is frequently used in radiosurgery [36], [37] and stereotactic surgery but the potential for residual error must be borne in mind.…”
Section: Discussionmentioning
confidence: 99%
“…17. Merge the CT images with the MRI images in the stereotactic navigation software 28,29 . Click on the paired volumetric CT and MRI images underneath the "Fusion" tab and then click "Auto Fusion".…”
Section: Introductionmentioning
confidence: 99%
“…MRI scans are more susceptible to spatial distortion due to a number of factors, including inhomogeneities of the constant magnetic field, nonlinearity of the gradient field, linear scale error, instrument imperfections, magnetic susceptibility artefacts and the effects of local magnetization [17,21,[25][26][27]. Several authors have suggested that image fusion with CT scans may improve the accuracy of spatial targeting over that achieved using MRI alone [21,[28][29][30][31]. CT-MR image fusion is increasingly used for stereotactic DBS electrode placement, but we could not find any article underscoring the amount of information that can be derived by the fusion of the postoperative MRI with the pre-operative stereotactic CT.…”
Section: Discussionmentioning
confidence: 99%